ANALYSIS OF THE INFLUENCE OF BANK HEALTH LEVEL WITH RGEC METHOD ON FINANCIAL DISTRESS USING ALTMAN Z-SCORE METHOD - Patricia, Chika; Setijaningsih, Herlin Tundjung; Verawati , Verawati (Graduate Program of Universitas Tarumanagara, 2024)
Amidst economic and market dynamics, various business sectors, including banks, confront challenges that can lead to financial distress or potential bankruptcy. This distress is influenced by various factors, among which is the health level of banks. This research aims to provide empirical evidence on the influence of bank health level, assessed by the RGEC method, on financial distress. The independent variables include Risk Profile, Good Corporate Governance, Earnings, and Capital, while the Altman Z-score measures financial distress as the dependent variable. Focused on banking companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022, this research utilized a purposive sampling approach, selecting 29 samples and totalling 87 data sourced from financial statements and annual reports, which underwent analysis via multiple linear regression using Eviews version 12. The results show that the Risk Profile and Good Corporate Governance do not have a significant influence on financial distress. Meanwhile, Earnings and Capital have a positive and significant influence on financial distress. This research can serve as an early warning for management regarding bankruptcy risks and provide insights for banks regulators and policymakers to fortify risk management practices and strategize adjustments to mitigate the risk of financial distress.